PERFORMANCE OF RED TILAPIA IN THREE DIFFERENT LEVELS OF SALINITY - Didik Ariyanto; Muslikhin Muslikhin (Indonesian Aquaculture Journal, 2011)
Tilapias are indigeneous species to Africa, but interest in their aquaculture potential has led to nearly worldwide distribution of the species within the past fifty years. The most popular species of tilapias cultured in the world is Oreochromis niloticus. Red tilapia, one of tilapia varieties, is a highly valued commodity in global market. Based on this reason, red tilapia culture should be developed to supply the market demand. Tilapias can be culturred in brackishwater ponds due to its tolerant ability to saline water. This study was carried out to know the potential of tilapia especially the NIFI red tilapia cultured in saline water. The seeds of NIFI red tilapia were reared in three levels of salinity, i.e. 10, 20, and 30 ppt with 0 ppt as the control population. The experiment was conducted in wet laboratory for 56 days. The results showed that the difference of salinity level did not affect the performance of NIFI red tilapia, including specific growth rate, survival rate, total biomass, and food conversion ratios. Based on these results, it is suggested that NIFI red tilapia can be cultured in saline waters.